1991
DOI: 10.1038/349529a0
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous retrovirus mediating deletion of αβ T cells?

Abstract: A special class of self-antigens (endogenous superantigens) is capable of deleting many murine T cells on the basis of their expression of particular T-cell receptor V beta gene segments. In mice that endogenously express these antigens, tolerance is mediated in part by the clonal deletion of the relevant V beta-bearing T cells. The deletion of I-E-reactive V beta 5.2-bearing T cells is dependent on the coexpression of an I-E tolerogenic coligand (Etc)14 and the gene for one of these coligands, Etc-1, maps to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(106 citation statements)
references
References 28 publications
4
100
2
Order By: Relevance
“…The role of H-2 k product(s) was confirmed by the lack of V~20 expression in the congenic B6.H-2L The strain distribution of V320 expression follows that observed for V~lTa1 and V311, which are controlled in I-Epositive mice by two kinds of self superantigens: a nonpolymorphic B cell-specific product of an unknown nature mediates the deletion of V317al-bearing T cells (13,14), and integrated sequences related to mouse mammary tumor virus prevent V1311 expression (15)(16)(17) specificity toward deleting elements are located in a loop distant from the site of interaction with MHC/antigenic peptide complex (18). Minor alterations in this region of VB17a1 drastically alter its reactivity toward Mls2/3 (10).…”
Section: Expression Of V320 Studies Of V3 Usage By Stainings Withmentioning
confidence: 92%
See 1 more Smart Citation
“…The role of H-2 k product(s) was confirmed by the lack of V~20 expression in the congenic B6.H-2L The strain distribution of V320 expression follows that observed for V~lTa1 and V311, which are controlled in I-Epositive mice by two kinds of self superantigens: a nonpolymorphic B cell-specific product of an unknown nature mediates the deletion of V317al-bearing T cells (13,14), and integrated sequences related to mouse mammary tumor virus prevent V1311 expression (15)(16)(17) specificity toward deleting elements are located in a loop distant from the site of interaction with MHC/antigenic peptide complex (18). Minor alterations in this region of VB17a1 drastically alter its reactivity toward Mls2/3 (10).…”
Section: Expression Of V320 Studies Of V3 Usage By Stainings Withmentioning
confidence: 92%
“…VB20 was amplified with KgDO (complementary to positions 472-488 of V1520) and XNSC10. V~20-specific PCtLs were done with KguP (positions 241-256 of VB20) and MTB primers, of TCR B transcripts with the MCTBUP (positions [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and an equimolar mixture of the MTB1DO and MTB2DO primers (complementary to positions 474-493 of C131 and C132), of TCR c~ transcripts with MTCAUP (positions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and MTCADO2 primers (complementary to positions 263-279), and of V1317 with MVB17S and MVB17FX, as previously described (10).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has recently been demonstrated that endogenous Mtv retroviral sequences are homologous to Mls (minor lymphocyte stimulatory) superantigens and thus serve to alter the T cell repertoire (54)(55)(56)(57) …”
Section: Resultsmentioning
confidence: 99%
“…These are proteins that stimulate T cells bearing the appropriate V13 element almost independently ofcontributions from other parts of the TCRs borne by the T cells (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Such proteins, called superantigens because they stimulate large numbers ofT cells, are encoded by microorganisms including retroviruses, bacteria, and mycoplasma (22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%